The Large Core of College Admission Markets: Theory and Evidence - Biró, Péter; Hassidim, Avinatan; Romm, Assaf; Shorrer, Ran I.; Sóvágó, Sándor (The Review of Economics and Statistics, 2025)
We study college admissions markets where students can attend the same college under different financial terms. The deferred acceptance algorithm identifies a stable allocation where funding is allocated based on merit and the set of meritbased stable allocations is small. When students are heterogeneous in the way they trade off program characteristics and contractual terms, the set of stable allocations is large and different stable allocations differ in the number of assigned students. In Hungary, where such heterogeneity is present, a non-merit-based stable allocation would increase the number of assigned applicants by 1.9% relative to any merit-based stable allocation.